DIGITALIZATION OF THE LEARNING PROCESS, DISTANCE EDUCATION, AND PEDAGOGICAL-PSYCHOLOGICAL CALLENGES: AN ANALYTICAL STUDY (Ustozlar uchun, 2025)
This study examines the pedagogical and psychological problems that arise during the digitalization of the learning process, the implementation of distance education, and the use of modern educational technologies. Through analytical methods, the research identifies major challenges related to students’ motivation, digital literacy, cognitive load, teacher preparedness, and socio-emotional well-being.